Sistem Informasi Mahasiswa Asing - Robiansyah, Hari; Salma, Linda (MATICS, 2017)
Abstract—A residence permit is permission given to foreigners by Immigration Officials or foreign-service officer to be in the region of Indonesia in a certain period of time. Foreign students studying in Indonesia must have a residence permit in order to continue learning in Indonesia. Residence permit have a time limit and must always be extended before it expires (overstayed). Foreign student information system and a reminder of this residence permit are systems built to help foreign students of UIN Maulana Malik Ibrahim Malang in reminding the residence permit problems. This research uses Agile Development with Scrum model in development. GNU All Mobile Management Utilities (GAMMU) is used for sending SMS (Short Message Service), and Cron program is used for running SMS commands automatically each day. The results of this research are the foreign student information system and reminder that automatically provide reminder in the form of SMS to foreign students whose the validity period of residence permit will run out.